In vitro culture of hairy roots of the shrub, Phyllanthus acuminatus (Phyllanthaceae). - Pérez Méndez, Raquel (2022)
Introduction: Under natural conditions, the roots of the shrub, Phyllanthus acuminatus, produce low concentrations of secondary metabolites of medicinal interest. This opens an opportunity for in vitro culture, to increase metabolite concentration. Objective: To determine the optimal liquid culture conditions for hairy roots of P. acuminatus. Methods: We used biomass growth evaluation according to initial inoculum percentage (0.50 and 0.10 %), percentage of medium nutrients (100, 50 and 25 %) and agitation rate (90, 100 and 110 min-1) (N=15 replications). Results: The best liquid culture conditions were: 0.10 % of initial inoculum, nutrients at 25 % and 90 min-1 for the agitation rate. There are differences among hairy roots and non-transformed roots. Conclusions: it is feasible to produce P. acuminatus hairy roots at a large scale, applying and implementing the evaluated conditions of inoculum percentage, nutrients in the medium and agitation rates.